In vivo MRS measurement of 2‐hydroxyglutarate in patient‐derived IDH‐mutant xenograft mouse models versus glioma patients. Issue 3 (30th January 2020) - Tiwari, Vivek; Mashimo, Tomoyuki; An, Zhongxu; Vemireddy, Vamsidhara; Piccirillo, Sara; Askari, Pegah; Hulsey, Keith M.; Zhang, Shanrong; de Graaf, Robin A.; Patel, Toral R.; Pan, Edward; Mickey, Bruce E.; et al.
Abstract : Purpose: To generate a preclinical model of isocitrate dehydrogenase (IDH) mutant gliomas from glioma patients and design a MRS method to test the compatibility of 2‐hydroxyglutarate (2HG) production between the preclinical model and patients. Methods: Five patient‐derived xenograft (PDX) mice were generated from two glioma patients with IDH1 R132H mutation. A PRESS sequence was tailored at 9.4 T, with computer simulation and phantom analyses, for improving 2HG detection in mice. 2HG and other metabolites in the PDX mice were measured using the optimized MRS at 9.4 T and compared with 3 T MRS measurements of the metabolites in the parental‐tumor patients. Spectral fitting was performed with LCModel using in‐house basis spectra. Metabolite levels were quantified with reference to water. Results: The PRESS TE was optimized to be 96 ms, at which the 2HG 2.25 ppm signal was narrow and inverted, thereby leading to unequivocal separation of the 2HG resonance from adjacent signals from other metabolites. The optimized MRS provided precise detection of 2HG in mice compared to short‐TE MRS at 9.4 T. The 2HG estimates in PDX mice were in excellent agreement with the 2HG measurements in the patients. Conclusion: The similarity of 2HG production between PDX models and parental‐tumor patients indicates that PDX tumors retain the parental IDH metabolic fingerprint and can serve as a preclinical model for improving our understanding of the IDH‐mutation associated metabolic reprogramming.